2019
DOI: 10.3389/fneur.2019.00263
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epileptic Activity in Older Adults With Delirium, a Prospective Continuous EEG Study

Abstract: Background/Objectives: Delirium occurs in up to 50 % of hospitalized old patients and is associated with increased morbidity and mortality. Acute medical conditions favor delirium, but the pathophysiology is unclear. Preliminary evidence from retrospective and prospective studies suggests that a substantial minority of old patients with unexplained delirium have non-convulsive seizures or status epilepticus (NCSE). Yet, seeking epileptic activity only in unexplained cases of delirium might result in misinterpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 56 publications
(67 reference statements)
0
26
0
Order By: Relevance
“…Seizures are known to be associated with a poor outcome in patients in ICU (27) and can be found in patients with delirium of any cause and in patients with sepsis like the majority of our patients (2,28). The co-occurrence of seizures in septic patients may be seen as a potential marker of brain dysfunction with prognostic signi cance (2,28,29). On the other hand, presence of epileptiform activity may worsen and/or may even trigger delirium in some patients (30).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Seizures are known to be associated with a poor outcome in patients in ICU (27) and can be found in patients with delirium of any cause and in patients with sepsis like the majority of our patients (2,28). The co-occurrence of seizures in septic patients may be seen as a potential marker of brain dysfunction with prognostic signi cance (2,28,29). On the other hand, presence of epileptiform activity may worsen and/or may even trigger delirium in some patients (30).…”
Section: Discussionmentioning
confidence: 89%
“…Generalized EEG slowing (increased delta and theta frequency) is frequently found in patients with delirium (9,29). However slowing is also common in ICU patients and related with various causes of altered mental status, decreased arousal, including coma, sleep, and sedation (35).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 27 The co‐occurrence of seizures in septic patients may be seen as a potential marker of brain dysfunction with prognostic significance. 1 , 27 , 28 On the other hand, the presence of epileptiform activity may worsen and/or may even trigger delirium in some patients. 29 Periodic discharges without seizures were also more prominent in delirium patients; studies in neurologic ICU patients suggest that periodic discharges are independent predictors of poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm that SE is common in patients in neurocritical care, but the prevalence of seizure activity in this study is even higher than previously reported. A review of the literature on cEEG and detection of status epilepticus and seizures in adults published in the past 5 years are provided in Table 3 14,17–40 . 51–59 Most studies on seizures activity and cEEG performed in neurocritically ill patients are from the United States.…”
Section: Discussionmentioning
confidence: 99%